2014
DOI: 10.1103/physreve.90.062709
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-time-scale framework for understanding the progression of Parkinson's disease

Abstract: Parkinson's disease is marked by neurodegenerative processes that affect the pattern of discharge of basal ganglia neurons. The main features observed in the parkinsonian globus pallidus pars interna (GPi), a subdomain of the basal ganglia that is involved in the regulation of voluntary movement, are pathologically increased and synchronized neuronal activity. How these changes affect the implemented neuronal code is not well understood. Our experimental temporal structure-function analysis shows that in parki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…In particular, several authors offered evidence of complex time patterns in the neuronal activity of the basal ganglia (see for example the discussion in (Nambu 2005)). In previous work I analyzed first order structure functions (G = 1) of simulated, animal, and human spike trains, and hypothesized that time patterns and rate-coding properties coexist in the basal ganglia (Andres, Gomez et al 2014, Andres, Cerquetti et al 2015, Andres, Cerquetti et al 2016. Here I continue the study to higher orders (G > 1) and show that the scaling behavior of structure functions can be used to obtain the multifractal spectrum of the human, parkinsonian basal ganglia.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…In particular, several authors offered evidence of complex time patterns in the neuronal activity of the basal ganglia (see for example the discussion in (Nambu 2005)). In previous work I analyzed first order structure functions (G = 1) of simulated, animal, and human spike trains, and hypothesized that time patterns and rate-coding properties coexist in the basal ganglia (Andres, Gomez et al 2014, Andres, Cerquetti et al 2015, Andres, Cerquetti et al 2016. Here I continue the study to higher orders (G > 1) and show that the scaling behavior of structure functions can be used to obtain the multifractal spectrum of the human, parkinsonian basal ganglia.…”
Section: Discussionmentioning
confidence: 83%
“…However, the role of these so called passive electric properties of neuronal activity is rarely considered in neurophysiology studies, which usually focus on spiking activity. Previous modeling work on the basal ganglia by our group has shown that a diffusion coefficient might be a critical parameter for the control of information transmission and information deterioration in the parkinsonian GPi [31]. The model introduced here shows that: 1. multifractality of neuronal spike trains depends on diffusive properties, and 2. multifractality of temporal activity is reflected on the spatial domain.…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations